Scapular dyskinesis increases the risk of future shoulder pain by 43% in asymptomatic athletes: a systematic review and meta-analysis - Hickey, Darren; Solvig, Veronica; Cavalheri, Vinicius; Harrold, Megan; McKenna, Leanda (BMJ Group, 2018)
Background: It is unclear whether the presence of scapular dyskinesis increases the risk of developing shoulder pain in asymptomatic athletes. Objectives: To determine whether the presence of scapular dyskinesis in asymptomatic athletes increases the risk of developing shoulder pain by systematic review and meta-analysis. Methods: A systematic search was conducted in the Cochrane Library, Embase, PubMed, Cumulative Index to Nursing and Allied Health Literature, Allied and Complementary Medicine Database and SPORTDiscus. Prospective studies that assessed athletes for scapular dyskinesis and recorded incidents of shoulder pain were included. Study quality was assessed using the Downs and Black checklist. Meta-analysis was conducted to derive a pooled risk ratio (RR) for the development of shoulder pain in athletes with scapular dyskinesis compared with those without scapular dyskinesis. Results: Five studies were included with a total of 419 athletes. Of the athletes with scapular dyskinesis, 35% (56/160) experienced shoulder pain during the follow-up, whereas 25% (65/259) of athletes without scapular dyskinesis experienced symptoms. The presence of scapular dyskinesis at baseline indicated a 43% increased risk of a shoulder pain event over a 9 to 24 months follow-up (RR=1.43, 95% CI 1.05 to 1.93). Conclusions: Athletes with scapular dyskinesis have 43% greater risk of developing shoulder pain than those without scapular dyskinesis.